Disaster-oriented guidance program of professional school counselors: A systematic literature review - Ficky Adi Kurniawan; Wahyu Nanda Eka Saputra; Irvan Budhi Handaka; Lutfi Aji; Dicky Fransisco Simanjuntak (Journal of Professional Teacher Education, 2026)
Guidance program services play a strategic role in strengthening students' disaster preparedness by enhancing psychological readiness, social competence, and adaptive behavior in educational settings.  This study investigates how guidance program services contribute to strengthening students’ disaster preparedness while also exploring the challenges encountered in implementing these services within school settings.  Guidance program services are defined as developmental and preventive interventions delivered systematically through classroom guidance, information services, group guidance, and psychoeducational activities to strengthen students' personal, social, and adaptive competencies.  This study used a systematic literature review (SLR) of peer-reviewed national and international articles published between 2018 and 2025. The search identified 24 articles, and 17 were selected based on their relevance, quality, research methods, and suitability to the topic. The review was conducted in four stages: identification, screening, eligibility, and inclusion. The findings indicate that information services, classroom guidance, and psychosocial support significantly improve students' disaster awareness, preparedness, resilience, emotional readiness, and adaptive responses. However, the integration of Guidance and Counseling services into Disaster-Safe School programs remains limited and largely conceptual, with few sustainable implementation models. These findings suggest that disaster preparedness should address psychological and emotional resilience alongside physical readiness. Therefore, developing adaptive, integrated, and evidence-based disaster-oriented Guidance and Counseling service models is essential for strengthening school disaster preparedness and fostering safe, inclusive, and disaster-resilient educational environments. The findings also provide directions for future research on disaster-oriented counseling interventions across diverse educational contexts.